Implementasi Metode Sorogan dalam Meningkatkan Pemahaman Santri pada Materi Kitab Kuning Mabadi'ul Fiqih di Pondok Pesantren Al-Anwar - Syihabuddin; Sholihul Anshori (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2019)
This Sorogan method system is considered a very difficult phase of the entire boarding school teaching system, because it demands patience, diligence, obedience and discipline of the students themselves, with this system I require students to actively learn in teaching and learning activities. This study aims to find out about the implementation of the sorogan method in improving the understanding of the santri about the yellow book at Al-Anwar Pacul Gowang Diwek Islamic Boarding School, Jombang. There are three problems in this research, namely: (1) How to increase students 'understanding of the yellow book through the sorogan system in understanding the mabadi' fiqih book; (2) How are the efforts to improve students' understanding of the yellow book through the sorogan method; (3) What are the supporting and inhibiting factors in increasing students' understanding of the yellow book through the sorogan method system. This type of research is a qualitative field, with a descriptive approach because this research only reveals and describes the data as it is based on facts that arise or occur at the time the research was carried out. The presence of researchers as non-participants because they are only observers. Data collection techniques using interviews, observation and documentation. Data analysis techniques use domain analysis. Checking the validity of data, persistence of observations, triangulation, referential adequacy and member checks. The results of the research on the implementation of the sorogan method system in improving students' understanding of the yellow book at Al-Anwar Islamic Boarding School. In their daily life, the students learn about the yellow book. In its delivery the teachers or ustadz are different methods used. One of them is the Sorogan method system. In this case the system of views is very positive. In this case the students said there were many benefits from the sorogan method. The sorogan method system is implemented inside the classroom and outside the classroom, especially in the Al-Anwar male Islamic boarding school. Constraints that occur during the method system include: their sense of ego in expressing opinions, lack of availability of reference books